1986
DOI: 10.1055/s-2008-1054103
|View full text |Cite
|
Sign up to set email alerts
|

Erfahrungen mit der intradiskalen Injektionsbehandlung mit Chymopapain und Kollagenase

Abstract: In a comparative study 71 patients were treated by intradiscal injection of collagenase and 93 patients by chymopapain injections. Indication, technique of injection and post-injection treatment were based on uniform criteria and followed standardised procedure. In practically all cases, monosegmental injections were performed almost exclusively in the last two discs of the lumbar vertebral column; in cases where the x-ray and clinical findings were unequivocal, the injections were performed at one level of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The results showed that collagenase had no long-term effect on the structure and function of the nerve fibres 29. The same conclusion was reached in clinical trials 30. Other animal experiments or clinical treatment of intradiscal injection of collagenase chemonucleolysis also achieved good results 31–33…”
Section: Collagenase Chemonucleolysissupporting
confidence: 56%
“…The results showed that collagenase had no long-term effect on the structure and function of the nerve fibres 29. The same conclusion was reached in clinical trials 30. Other animal experiments or clinical treatment of intradiscal injection of collagenase chemonucleolysis also achieved good results 31–33…”
Section: Collagenase Chemonucleolysissupporting
confidence: 56%